Archetypes of climate change adaptation among large-scale arable farmers in southern Romania - Necula, Cristiana (2024)
Effects of climate change and especially the associated climate variability require farmers to adjust to increasing frequencies of extreme events. In the agriculturally highly productive Romanian Plain, the frequency, intensity, and duration of heatwaves and drought have increased over the past 20 years. Although recent surveys revealed farmers’ awareness of climate change and enumerated a number of farm adaptation measures in the Romanian context, a systems approach to adaptation that allows conclusions on farm vulnerability and adaptive capacity is missing. Here, we use archetypal analysis to elucidate and characterize for the first time the types of adaptation responses of arable farmers in southern Romania. We conducted semi-structured interviews with 30 farmers managing 51,500 ha located across the southern lowlands of Romania, selected for their diversity of management approaches. Farmers were asked about experienced climatic disturbances, crop production losses during the most extreme events over the past 5–10 years, and the adaptation measures they implemented over that period of time. In addition, structural characteristics of the farm were recorded. The adaptation measures were classified and mapped on the efficiency, substitution, and redesign gradient used to classify sustainability stages. Results revealed three archetypes of adaptation, consisting of measures at field and farm level ranging from predominantly efficiency-enhancing ones (e.g., crop choice and management and risk insurance) to complete farm redesign involving agrotechnical and financial management changes. Structural farm characteristics did not explain differences between farms in their association with one of the archetypes. Our approach and results show for the first time both the need for strengthening farmer-level support in one of Europe’s key food production areas and the lessons that can be drawn from the outlier adaptation examples. Current European and national policies offer opportunities for farmer organizations in Romania to make these conclusions actionable.